Development of Descriptive Text Learning E-Module with a Constructivistic Approach - Puja Murdianto; Aunurrahman Aunurrahman; Indri Astuti (JETL (Journal of Education, Teaching and Learning), 2021)
The main objective of this research is to develop learning e-modules in teaching English in the classroom as well as to produce and disseminate learning media. This e-module can be used on smartphones and this e-module uses a constructivist approach. The steps of the research model are defined, designed, developed, and disseminated/implemented. Participants in this study were teachers and students of MAN 3 Pontianak. The data collection technique in this study refers to the interview list guidelines, namely the questionnaire. Data collection tools are learning outcomes and questionnaire sheets. This study uses a qualitative descriptive approach for data analysis. The results showed that the design of the electronic module learning development in this study consisted of an analysis of curriculum and learning materials, an analysis of the characteristics of students and an analysis of student learning outcomes. The steps for developing an electronic module are by submitting a lot of learning materials and then being reviewed by experts according to their backgrounds as media experts and learning materials experts. The results of the expert review showed that the average score of the electronic module was 3.77 (range 1 - 4) and also the test given to students before applying it. The response of students after using the e-module showed 83.2% which means a positive response. This e-module can be applied to students because it has criteria such as self-instruction, stand alone, adaptive and user friendly. The learning outcomes of this research are that students are more active and construct themselves in learning descriptive texts in English class. The Minimum Completeness Criteria (KKM) in this study is 75 and the average is 79.04, which means that the use of e-modules in teaching descriptive texts is effective and can increase their scores.